Untangling Quantitative Lichen Diversity in and Around Badrinath Holy Pilgrimage of Western Himalaya, India - Gupta, Sugam; Bajpai, Omesh; Rai, Himanshu; Upreti, Dalip Kumar; Sharma, Pradeep Kumar; Gupta, Rajan Kumar (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*411.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90638);" role="presentation">The present study was conducted in <span dir="ltr" style="left: calc(var(–scale-factor)*219.53px); top: calc(var(–scale-factor)*411.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*234.53px); top: calc(var(–scale-factor)*411.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942567);" role="presentation">Badrinath holy pilgrimage <span dir="ltr" style="left: calc(var(–scale-factor)*343.51px); top: calc(var(–scale-factor)*411.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99871);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*354.07px); top: calc(var(–scale-factor)*411.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923008);" role="presentation">Western Himalaya. <span dir="ltr" style="left: calc(var(–scale-factor)*434.47px); top: calc(var(–scale-factor)*411.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944576);" role="presentation">Lichen collected from <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*424.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.979903);" role="presentation">seven localities (<span dir="ltr" style="left: calc(var(–scale-factor)*144.26px); top: calc(var(–scale-factor)*424.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920987);" role="presentation">Badrinath, <span dir="ltr" style="left: calc(var(–scale-factor)*191.33px); top: calc(var(–scale-factor)*424.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883401);" role="presentation">enroute <span dir="ltr" style="left: calc(var(–scale-factor)*226.25px); top: calc(var(–scale-factor)*424.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01547);" role="presentation">Bhimpul to <span dir="ltr" style="left: calc(var(–scale-factor)*279.17px); top: calc(var(–scale-factor)*424.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901733);" role="presentation">Vasudhara<span dir="ltr" style="left: calc(var(–scale-factor)*322.03px); top: calc(var(–scale-factor)*424.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.983411);" role="presentation">, Mana, <span dir="ltr" style="left: calc(var(–scale-factor)*359.83px); top: calc(var(–scale-factor)*424.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883401);" role="presentation">enroute <span dir="ltr" style="left: calc(var(–scale-factor)*394.75px); top: calc(var(–scale-factor)*424.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904252);" role="presentation">Vasudhara <span dir="ltr" style="left: calc(var(–scale-factor)*442.78px); top: calc(var(–scale-factor)*424.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00158);" role="presentation">to Mana, Bhimpul, <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*437.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899633);" role="presentation">Vasudhara <span dir="ltr" style="left: calc(var(–scale-factor)*118.10px); top: calc(var(–scale-factor)*437.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924047);" role="presentation">Glacier and <span dir="ltr" style="left: calc(var(–scale-factor)*168.62px); top: calc(var(–scale-factor)*437.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883401);" role="presentation">enroute <span dir="ltr" style="left: calc(var(–scale-factor)*201.89px); top: calc(var(–scale-factor)*437.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917198);" role="presentation">Vasudhara to <span dir="ltr" style="left: calc(var(–scale-factor)*259.01px); top: calc(var(–scale-factor)*437.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944546);" role="presentation">Bhagirathi Glacier)<span dir="ltr" style="left: calc(var(–scale-factor)*337.27px); top: calc(var(–scale-factor)*437.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969827);" role="presentation">. The highest overall IVI <span dir="ltr" style="left: calc(var(–scale-factor)*442.30px); top: calc(var(–scale-factor)*437.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923682);" role="presentation">(6.64) <span dir="ltr" style="left: calc(var(–scale-factor)*469.78px); top: calc(var(–scale-factor)*437.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896733);" role="presentation">was recorded <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*450.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*86.42px); top: calc(var(–scale-factor)*450.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913118);" role="presentation">Rhizoplaca <span dir="ltr" style="left: calc(var(–scale-factor)*134.30px); top: calc(var(–scale-factor)*450.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907925);" role="presentation">chrysoleuca<span dir="ltr" style="left: calc(var(–scale-factor)*182.54px); top: calc(var(–scale-factor)*450.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922837);" role="presentation">. The maximum number of lichens have been documented in Badrinath locality (139 <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*463.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95616);" role="presentation">spp.) while minimum (6) in <span dir="ltr" style="left: calc(var(–scale-factor)*186.02px); top: calc(var(–scale-factor)*463.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886643);" role="presentation">enroute <span dir="ltr" style="left: calc(var(–scale-factor)*218.81px); top: calc(var(–scale-factor)*463.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902153);" role="presentation">Vasudhara <span dir="ltr" style="left: calc(var(–scale-factor)*264.41px); top: calc(var(–scale-factor)*463.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936231);" role="presentation">to Bhagirathi Glacier. The Badrinath <span dir="ltr" style="left: calc(var(–scale-factor)*415.15px); top: calc(var(–scale-factor)*463.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.822971);" role="presentation">has <span dir="ltr" style="left: calc(var(–scale-factor)*431.23px); top: calc(var(–scale-factor)*463.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903401);" role="presentation">also express maximum <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*477.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948481);" role="presentation">71 site specific species, while the <span dir="ltr" style="left: calc(var(–scale-factor)*215.09px); top: calc(var(–scale-factor)*477.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902153);" role="presentation">Vasudhara <span dir="ltr" style="left: calc(var(–scale-factor)*261.65px); top: calc(var(–scale-factor)*477.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947999);" role="presentation">Glacier has only 2 spec<span dir="ltr" style="left: calc(var(–scale-factor)*359.95px); top: calc(var(–scale-factor)*477.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920405);" role="presentation">ies. The dominance has been computed <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*490.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972014);" role="presentation">maximum (0.17) for <span dir="ltr" style="left: calc(var(–scale-factor)*159.98px); top: calc(var(–scale-factor)*490.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883401);" role="presentation">enroute <span dir="ltr" style="left: calc(var(–scale-factor)*193.73px); top: calc(var(–scale-factor)*490.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899633);" role="presentation">Vasudhara <span dir="ltr" style="left: calc(var(–scale-factor)*240.29px); top: calc(var(–scale-factor)*490.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976842);" role="presentation">to Bhagirathi Glacier while, minimum for the Badrinath (0.01). The <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*503.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951416);" role="presentation">lowest Simpson Index value (0.83) has been recorded in <span dir="ltr" style="left: calc(var(–scale-factor)*312.77px); top: calc(var(–scale-factor)*503.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883401);" role="presentation">enroute <span dir="ltr" style="left: calc(var(–scale-factor)*346.75px); top: calc(var(–scale-factor)*503.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899423);" role="presentation">Vasudhara <span dir="ltr" style="left: calc(var(–scale-factor)*393.55px); top: calc(var(–scale-factor)*503.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.966865);" role="presentation">to Bhagirathi Glacier <span dir="ltr" style="left: calc(var(–scale-factor)*485.14px); top: calc(var(–scale-factor)*503.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967907);" role="presentation">while <span dir="ltr" style="left: calc(var(–scale-factor)*511.18px); top: calc(var(–scale-factor)*503.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*516.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935899);" role="presentation">highest (0<span dir="ltr" style="left: calc(var(–scale-factor)*113.06px); top: calc(var(–scale-factor)*516.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968413);" role="presentation">.99) in Badrinath. The lowest value of Berger-<span dir="ltr" style="left: calc(var(–scale-factor)*307.73px); top: calc(var(–scale-factor)*516.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96631);" role="presentation">Parker diversity index (<span dir="ltr" style="left: calc(var(–scale-factor)*405.79px); top: calc(var(–scale-factor)*516.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95043);" role="presentation">0.03), as well as the highest <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*530.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923933);" role="presentation">values of Brillouin, Shannon, Menhinick, Margalef and Fisher alpha diversity indices (7.20, 4.78, 8.03, 24.2 and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*543.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922475);" role="presentation">100.6 respectively) from the Badrinath loca<span dir="ltr" style="left: calc(var(–scale-factor)*247.01px); top: calc(var(–scale-factor)*543.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.10402);" role="presentation">lity, <span dir="ltr" style="left: calc(var(–scale-factor)*265.37px); top: calc(var(–scale-factor)*543.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.879869);" role="presentation">designates it as a site <span dir="ltr" style="left: calc(var(–scale-factor)*352.39px); top: calc(var(–scale-factor)*543.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918994);" role="presentation">of highest <span dir="ltr" style="left: calc(var(–scale-factor)*394.75px); top: calc(var(–scale-factor)*543.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933296);" role="presentation">species diversity. While <span dir="ltr" style="left: calc(var(–scale-factor)*493.42px); top: calc(var(–scale-factor)*543.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886643);" role="presentation">enroute <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*556.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899633);" role="presentation">Vasudhara <span dir="ltr" style="left: calc(var(–scale-factor)*117.38px); top: calc(var(–scale-factor)*556.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9265);" role="presentation">to Bhagirathi Glacier locality shows the highest value of Berger-<span dir="ltr" style="left: calc(var(–scale-factor)*377.11px); top: calc(var(–scale-factor)*556.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928282);" role="presentation">Parker diversity index (0.17) as well <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*569.86px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938569);" role="presentation">as the lowest values of Brillouin, Shannon, Menhinick, Margalef and F<span dir="ltr" style="left: calc(var(–scale-factor)*360.79px); top: calc(var(–scale-factor)*569.86px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928435);" role="presentation">isher alpha diversity indices (1.75, 1.79, <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*583.06px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930163);" role="presentation">0.35, 0.88 and 1.03 respectively). The value of evenness and equitability has been computed maximum (1.00) <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*596.26px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*87.50px); top: calc(var(–scale-factor)*596.26px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883401);" role="presentation">enroute <span dir="ltr" style="left: calc(var(–scale-factor)*121.22px); top: calc(var(–scale-factor)*596.26px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902153);" role="presentation">Vasudhara <span dir="ltr" style="left: calc(var(–scale-factor)*167.90px); top: calc(var(–scale-factor)*596.26px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94709);" role="presentation">to Mana and <span dir="ltr" style="left: calc(var(–scale-factor)*224.33px); top: calc(var(–scale-factor)*596.26px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902153);" role="presentation">Vasudhara <span dir="ltr" style="left: calc(var(–scale-factor)*271.01px); top: calc(var(–scale-factor)*596.26px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.966479);" role="presentation">to Bhagirathi Glacier localities, on the other hand, minimum (<span dir="ltr" style="left: calc(var(–scale-factor)*75.38px); top: calc(var(–scale-factor)*609.58px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910897);" role="presentation">0.086 and 0.97 respectively) in the Badrinath